Metodologia para determinação da retenção de água pelo campo nativo do bioma Pampa - Jaeger, Cabrieli Aline (2022)
The lack of information about the existing relationship between the native field’s herbaceous vegetation and hydrological processes runs through the years, and makes it impossible to measure the impact that this change of the soil natural covering can cause in a river basin. Thus, this present paper had as general objective to evaluate the rain simulators as a method to determine the water retention by native and serrapilheira vegetation of Pampa Biome; and as specific objectives, contribute to the method of water retention determination by herbaceous vegetation: evaluate applicability of the rain simulator as a method to determine water retention by native and serrapilheira vegetation of the Pampa Biome; and estimate water intercepted by the air and root vegetation, using local rainwater data. The methodology used was the field research taken in Rosários do Sul town, in 2014, and in Caçapava do Sul, in 2021; where a rain simulator, structured samples of native field and soil vegetation, to the application of rain tests at 100 mm.h -1 , in order to determine the quantity of water that gets retained in herbaceous plants. From this, an estimation of water retention by vegetation during rainy events was made, from historical rainfall data. Numbers found were 13,2% retention to Rosário do Sul’s vegetation and 4,5% to Caçapava do Sul’s vegetation; showing an overall average of 8,9% of total rainfall incidence to this biome. The method used in this present paper showed itself as a favorable alternative for obtaining data on water retention by native field herbaceous vegetation, because, besides its limitations, numbers observed were similar to the ones found in literature. However, due to the uncertainties the method presents, especially to sensitivity to efficiently register a small portion of retained water; to the difficulty in obtaining samples with equal thickness, and to the association between root and air parts of the plant, it is necessary to hold methodological adjustments in order to increase the accuracy of data.